The Impact of Bank Regulations, Concentration, and Institutions on Bank Margins - Demirguc-Kunt, Asli; Laeven, Luc; Levine, Ross (World Bank, Washington, DC, 2014)
This paper examines the impact of bank regulations, concentration, inflation, and national institutions on bank net interest margins using data from over 1,400 banks across 72 countries while controlling for bank-specific characteristics. The data indicate that tighter regulations on bank entry and bank activities boost net interest margins. Inflation also exerts a robust, positive impact on bank margins. While concentration is positively associated with net interest margins, this relationship breaks down when controlling for regulatory impediments to competition and inflation. Furthermore, bank regulations become insignificant when controlling for national indicators of economic freedom or property rights protection, while these institutional indicators robustly explain cross-bank net interest margins. So, bank regulations cannot be viewed in isolation. They reflect broad, national approaches to private property and competition.